The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.24171/j.phrp.2020.11.5.09
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antimicrobial Susceptibility, Extended-Spectrum β-Lactamase Genes and Phylogenetic Groups of Enteropathogenic <italic>Escherichia coli</italic> Isolated from Patients with Diarrhea

Abstract: Objectives Infectious diarrhea is one of the most common causes of pediatric death worldwide and enteropathogenic Escherichia coli (EPEC) is one of the main causes. There are 2 subgroups of EPEC, typical and atypical, based on the presence or absence of bundle forming pili (bfp), of which atypical EPEC is considered less virulent, but not less pathogenic. Antimicrobial resistance towards atypical EPEC among children is growing and is considered a major problem. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Similar studies conducted in Iran and in Uganda have reported low rates of phylogroup E (Iranpour et al, 2015;Katongole et al, 2019). The possible source of DEC in this phylogroup could have been from animal feacal matter (Bagheri et al, 2014;Iranpour et al, 2015;Jafari et al, 2020).…”
Section: Phylogroup Analysissupporting
confidence: 63%
“…Similar studies conducted in Iran and in Uganda have reported low rates of phylogroup E (Iranpour et al, 2015;Katongole et al, 2019). The possible source of DEC in this phylogroup could have been from animal feacal matter (Bagheri et al, 2014;Iranpour et al, 2015;Jafari et al, 2020).…”
Section: Phylogroup Analysissupporting
confidence: 63%
“…Also, resistance may occur as a result of the modification of the target site of the PBPs (penicillin binding proteins), which is specialized in binding this antigen, which becomes ineffective [16]. Likewise, the frequent use of beta-lactam antibiotics in the treatment of many pathological conditions such as blood poisoning, food poisoning, and urinary tract infection led to the emergence of strains that are resistant to these antibiotics with the passage of time [17]. And as shown in As for the antibiotics belonging to the group of aminoglycosides, the results showed a discrepancy in their effect on P.mirabilis bacteria, where the bacteria were sensitive to the anti-Amikacin and moderately resistant to the anti-Gentamicin, and this result approached what was reached by [18] as they found that the resistance rate of a group of isolates P.mirabilis for the anti-Amikacin was 17.39%.…”
Section: Antibiotic Resistance Test Of Pmirabilismentioning
confidence: 99%